Industry - Academia Convergence: "Bridging The Skill Gap" Management Education in India - A Case Study - Singh, Anchal (Prabandhan: Indian Journal of Management, 2010)
Although India’s higher education system contributes about 350,000 engineers and 2.5 million university graduates annually to our workforce, yet at any given time, about 5 million graduates remain unemployed. According to a survey conducted by McKinsey Global Institute, it has been observed that MNCs find only 25 percent of Indian engineers employable, whereas a NASSCOM report foresees paucity of 500,000 knowledge workers by 2010. India warrants for over 10,000 PhDs (predicted by UR Rao Committee) and twice as many M. Tech degree holders for satisfying the growing needs of R&D but in reality, India produces only 400 engineering PhDs a year.